A REVIEW OF COMPOSITE BRIDGE GIRDER OF COLD-FORMED STEEL PLATE AND RC DECK - Allami, Ali; Majeed, Fareed H.; Hussain, Haleem K. (International Journal Multidisciplinary (IJMI), 2026)
Objective: This paper presents a review of earlier studies on the behavior of composite bridge girders made up of reinforced concrete (RC) decks and cold-formed steel plates. The objective is to examine the behavior of cold-formed steel composite girders under different load conditions and identify gaps in the research, especially concerning various cold-formed steel sections. Method: The behavior of cold-formed steel bridge girders was classified based on the loads applied and the shape of the cold-formed steel plate. Experimental and analytical studies have been conducted on cold-formed steel tub bridge girders and cold-formed steel tub bridge systems. Results: The study indicates that research on cold-formed steel bridge girders has focused mainly on steel tub sections, with limited research on other shapes, such as the double-C steel section. The studies considered different loads applied to the composite bridge girders, but there is a gap in understanding the behavior of various shapes of cold-formed steel girders. Novelty: The novelty of this paper lies in its identification of the lack of research on the double-C steel section of cold-formed composite girders and the need for additional studies. Future research should focus on the ductility, ultimate capacity under static and fatigue loads, and the interaction degree effect on the behavior of cold-formed composite girders. This will help fully comprehend the behavior of different cold-formed composite girder sections.